Эволюционная экономика как альтернатива налоговой неоклассике - Мазур, Ю.А. (Економіка промисловості, 2013)
Розглянуто фундаментальні положення
неокласичної економічної теорії у сфері оподаткування, які спираються на передумови щодо Парето-ефективного розподілу благ, раціональної поведінки індивідів в умовах повної інформованості і рівноваги ринків на короткострокових інтервалах часу. Обґрунтовано межі застосування неокласичних моделей оподаткування як інструменту прикладного дослідження в умовах обмеженої раціональності індивідів і нестабільності зовнішнього середовища.
Ключові слова: неокласична економічна теорія, моделі оподаткування, еволюційна економіка, еволюційні моделі. Рассмотрены фундаментальные положения неоклассической экономической теории в сфере налогообложения, которые опираются на предпосылки о Парето-эффективном распределении благ, рациональном поведении индивидов в условиях полной информированности и о равновесии рынков на краткосрочных интервалах времени. Обоснованы пределы применения неоклассических моделей налогообложения как инструмента прикладного исследования в условиях ограниченной рациональности индивидов и нестабильности внешней среды.
Ключевые слова: неоклассическая экономическая теория, модели налогообложения, эволюционная экономика, эволюционные модели. The fundamental principles of the neoclassical economic theory are considered, which are based on the precondition of Pareto efficient allocation of goods, rational behavior of fully informed individuals andequilibrium of markets at short intervals of time.The level of public welfare is the main aim of neoclassical investigations. There areRawlsian and Utilitarian approaches to the modeling of public welfare functions. The enterprise activities are described with production functions of various modifications, the consumers’ – of utility functions, the government – of budget constraints.In neoclassical economics the investigation of government regulation of the economy is reflected in the models of taxation, which represents the impact of taxes on economic growth. These models of taxation are descriptive and optimization.
Limits of neoclassical models of taxation as a tool for applied research in the limited rationality of individuals and the instability of the economic environment are established. These models do not take account of changes in the behavior of individuals.Therefore the conclusions of neoclassical economic theory need to be adjusted according to the institutional economic environment and the permanent changes in the economic activity of agents.
Evolutionary economics as scientific approach in the modern economic thought is a further development of the fundamental provisions of the orthodox theory. Using foundation of the neoclassical theory investigation, the evolutionary economics is aimed at a deeper study of the socio-economic processes and phenomena based on their long-term changes and changes in the behavior of agents who make certain decisions. Such decisions not always lead to an increase in public (or private) welfare. The need to consider the patterns of change of rules and norms of the individual's behavior in space and time in terms of their evolutionary development is identified.
The analysis of evolutionary models in modern economic theory has shown the feasibility of their use in the study of the tax influence on economic growth. These models are aimed at investigation of stochastic nonlinear (and non-equilibrium) states in the dynamics of the economy in terms of variability of the institutional environment and the impact of different market mechanisms. It is substantiated that evolutionary economics can be the basis of research of the influence of taxation on the economic growth in conditions of the changing status of studied objects.
Keywords: neoclassical economics, taxation models, evolutionary economics, evolutionary models.